Whatshisface - Korman, Gordon (New York Scholastic Press, 2018)
Twelve-year-old Cooper Vega and his military family has moved so often that he is used to new schoolmates not knowing his name, but at the moment he has a bigger problem--his new phone is haunted by the ghost of Roderick Northrop, a boy from the sixteenth-century, who needs his help to finish a quest, which is somehow tied up in the Stratford Middle School production of Romeo and Juliet.
Keywords: Shakespeare, William, -- 1564-1616 -- Authorship; Juvenile fiction; Shakespeare, William, -- 1564-1616 -- Juvenile fiction; Families of military personnel -- United States; Juvenile fiction; Cell phones -- Juvenile fiction; Secrecy -- Juvenile fiction; Friendship -- Juvenile fiction; Middle schools -- Juvenile fiction; Schools -- Juvenile fiction; Moving, Household -- Juvenile fiction; Ghost stories; Ghost stories; Detective and mystery fiction